Flora fanerogâmica de araceae do parque nacional do Caparaó, MG−ES, Brasil - Camelo, Mel de Castro (2018)
The species of Araceae are characterized by the presence of inflorescence in spadix, associated to a bract, the spathe. They occur in forest, country and rocky outcrops, presenting many endemic species. Some are highly adapted to specific habitats and few survive under altered conditions. The Caparaó National Park (ParNa Caparaó) has preserved areas and is recognized for the high endemism for species of Brazilian flora and high floristic richness. It is located in Serra do Caparaó, on the border of the states MG and ES, in southeastern Brazil. Located in one of the highest altitudes of the country, and about 70% of this conservation unit is in Espírito Santo. The region is occupied by semideciduous seasonal forest and dense ombrophylous forest at Montana and Upper Montana altitudes, as well as altitude fields. This work aims to inventory species of the Araceae family of the Caparaó National Park. The results are presented in two chapters, in article form, (Two new species of Anthurium Schott (Araceae) from Caparaó National Park, southeastern Brazil), where the first presents two new species of Anthurium sect. Urospadix Engl., which were found during the development of flora of Araceae from ParNa. And the second chapter (Araceae from Caparaó National Park, MG-ES, Brazil) deals with the inventory of Araceae, with 21 species belonging to four genera. In this are presented a key of identification of the species, descriptions, comments on phenology, geographic distribution, habitat and illustrations.